Comparing European workers. Part B, Policies and institutions - Brady, David, 1972-; Keister, Lisa A., 1968- (Bingley, U.K. : Emerald, 2011)
This second of two companion volumes places the labor markets, workplaces, jobs and workers of Europe in comparative perspective. It focuses on the politics, economics, sociology, and history of work and workers in Europe. It contains both qualitative and quantitative studies as well as explicitly theoretical work, and compares contemporary patterns and the recent history of European workers with other models of work worldwide. Authors contribute a variety of methodological and theoretical perspectives, with papers that push the boundaries of evidence and argument. Specific topics in 'Comparing European Workers Volume 2: Policies and Institutions' include: the political economy of active social policy in postindustrial democracies; social protection dualism, deindustrialization and cost containment; organized labor in Europe; and unionization in East European ex-communist countries. It asks such questions as 'does European-style welfare generosity discourage single mother employment?', 'whose interests do unions represent?' and 'are trade unions still redistributive?'.
Activating workers? : the political economy of active social policy in postindustrial democracies / Duane Swank -- Does European-style welfare generosity discourage single-mother employment? / Lane Destro, David Brady -- Social protection dualism, de-industrialization and cost containment / Martin Seeleib-Kaiser, Adam M. Saunders, Marek Naczyk -- From class to market : unionization in East European ex-Communist countries, 1990-2006 / Nathan D. Martin, Yunus Kaya -- Organized labor in Europe, 1960-2006 : persistent diversity and shared decline / Sanjay Pinto, Jason Beckfield -- Whose interests do unions represent? : unionization by income in Western Europe / Michael Becher, Jonas Pontusson -- Labor, globalization and inequality : are trade unions still redistributive? / Lucio Baccaro -- European workers : meaning-making beings / Caitlin Daniel, Eleni Arzoglou, Michèle Lamont.
Print version record
Keywords: Social Science -- Sociology -- General; Business & Economics -- Labor; Social Science -- General; Sociology: work & labour; Sociology; Foreign trade and employment -- Europe